The Realization of Conversational Implicatures in Listening Comprehension of â€˜Longman Preparation Course for the TOEFL Testâ€™ - Etik Khusnul Khotimah; Djanuarius Mujiyanto; Hendi Pratama (English Education Journal, 2022)
Studying implicatures cannot be separated from studying pragmatics. Studying pragmatics is studying meaning in context. Understanding meaning in context is very essential in communication. The purpose of the study was to explain the realization of idiosyncratic and formulaic conversational implicatures in listening comprehension section of â€˜LONGMAN Preparation Course for the TOEFL Testâ€™. Qualitative research is used to collect data, analyze the data, and take a conclusion based on the analysis of the findings. The type of qualitative study used is content analysis. In a TOEFL book titled LONGMAN Preparation Course for the TOEFL Test, data were implicatures in every conversation covered in the script of the short conversation of listening comprehension section. The researcher found that the four types of idiosyncratic implicature were all in the short conversations of listening comprehension section in the TOEFL book "LONGMAN Preparation Course for the TOEFL Test.â€ Meanwhile, formulaic implicature that could be found were idiomatic, scalar, sequential, and indirect criticism implicature. However, the other formulaic implicature such as pope-Q and MRR (Minimum Requirement Rule) could not be found. Finally, it is expected that the result of this research can provide scientific information about formulaic and idiosyncratic conversational implicature theory and practically improve students' awareness of formulaic and idiosyncratic implicature. It is also expected that it can help the students to do the listening comprehension section in every TOEFL test. Then, the results of this research can pedagogically be used to understand English better in its actual use and help learners better understand formulaic and idiosyncratic implicature.